Analysis Effectiveness of Use of Alocation Village Funds and Village Funds in Samba Danum Village Katingan Tengah Disrict on 2018 - samosir, Delima; ., Kristian; ., Miar (KnE Social Sciences, 2020)
This study aims to determine the effectiveness of the use of Allocation of Village Fund and Village Fund in Samba Danum Village in 2018. Sample in this research is Technical Team of Village financial management in Samba Danum Village. Data were collected by documentation method and interview. Data analysis uses effectiveness technique ratio. The results showed effective performance (99,9%). Level of effectiveness of village fund allocation management in Samba Danum Village in 2015 In Field of Implementation of Village Government (100%), Field of Implementation of Village Development (100%), Field of Community Development (100%), and The Budget Village Community Empowerment Sector (100%) According to realization. Year 2015 is the first year of Indonesia disbursed the Village Fund as mandated by constitution no. 6 Year 2014 about the Village. This fund is expected to be utilized by the village government to finance the administration, development and empowerment of rural communities. Allocation of village funds and Village Fund Expected to lift the area which is difficult to develop, so as to catch up from other regions. Keywords: Allocation Village Fund, Village Fund and Effectiveness